THE INFLUENCE OF THE JURIDICAL CIVIC CRITICAL LEARNING MODEL ON CRIMINAL LAW COURSES AS AN ENHANCEMENT OF STUDENTS' CRITICAL THINKING - Sundawa, Dadang; Muthaqin, Dwi Iman; Iswandi, Dede; Baeihaqi (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2021)
The juridical civic critical learning model is a combination of several other learning models such as the direct discussion learning model, the debate learning model and the jurisprudential inquiry learning model. The purpose of carrying out this research is to examine the level of knowledge, understanding, attitudes and behavior of students towards a criminal law incident and to increase it to a higher level. The juridical civic critical learning model trains students to be sensitive to social problems, take positions, towards these problems, and maintain these attitudes with relevant and valid arguments. Juridical civic critical learning model will later become a stimulus for students to increase critical thinking about social phenomena related to criminal law.